Review: Syméon le Studite. Discours Ascétique - Price, Richard M. (The journal of theological studies, 2003)
Syméon le Studite. Discours Ascétique Hilarion Alfeyev 154 Paris (Sources chrétiennes, 460.) Les Éditions du Cerf 2001 Paperback100F 2 204 06676 1